Advances in machinery, materials science and engineering application X proceedings of the 10th International Conference (MMSE 2024), Paris, France, 27-28 July 2024 - Giorgetti, Marco; Agarwal, Ramesh K. 1947-; Chen, Min (IOS Press, 2024)
Intro -- Title Page -- Preface -- About the Conference -- Contents -- Section 1. Mechanical Engineering and Advanced Manufacturing Technology -- Frequency Ratio Effects on Dynamic Behavior of Rotor-Bearing System -- Structure and Hydraulic Analysis of a 5-Ton Hydraulic Press by Simulation -- Hybrid Modeling of Rotor Systems Dynamics -- A Generative Approach to Mass Optimization of Wheel Assembly -- Design and Implementation of Salvage Device Structure with Camera Detection Function -- Research and Design of Hydraulic System for CNC Radial Drilling Special Machine Tool -- Optimization Design of Harmonic Drive Flexspline Fixture Based on Orthogonal Experiments -- Mechanical Analysis on the Frame of JC-17B Mobile Lifting Jack -- Mountain Micro Pile Drilling Rig and Micro Pile Foundation Construction Technology -- Design and Application of Loading System for Mine Reducer -- Structural Design of a Duck Bill Transplant Machine -- Evaluation of Technical Specifications of Rotary Friction Welding Machine Improved from Lathe -- Effect of Groove Depth on Herringbone Thrust Bearing Dynamic Coefficients -- Nonlinear Dynamic Behavior and Vibration Mechanism of a Large Range Rotating Elastic Beam Under Parallel Misalignment Constraints -- Design and Application of New Propulsion Mechanism for Construction Machinery -- Mechanical Analysis on Main Transmission Gear of High Efficiency Saw Blade Polishing Machine -- Design of Increasing Cutting Range for Cantilever Tunneling Machines Used in Coal Mines -- A Comparative Investigation into the Machining Characteristics of Low Carbon Steel Using Surfaced and Standard Cutting Tools -- Development of a Hydraulic Press for Composite Material Fabrication -- A Study on the Application of a New Design for Equal Channel Angular Pressing Die and Design Parameters -- Study on the Technological Design of Dielectric Support.
Open Access
Keywords: Konferenzschrift